2019
DOI: 10.1002/advs.201900678
|View full text |Cite
|
Sign up to set email alerts
|

Modulating Activity through Defect Engineering of Tin Oxides for Electrochemical CO2 Reduction

Abstract: The large‐scale application of electrochemical reduction of CO2, as a viable strategy to mitigate the effects of anthropogenic climate change, is hindered by the lack of active and cost‐effective electrocatalysts that can be generated in bulk. To this end, SnO2 nanoparticles that are prepared using the industrially adopted flame spray pyrolysis (FSP) technique as active catalysts are reported for the conversion of CO2 to formate (HCOO−), exhibiting a FEHCOO− of 85% with a current density of −23.7 mA cm−2 at an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
49
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 98 publications
(51 citation statements)
references
References 64 publications
2
49
0
Order By: Relevance
“…[37,54] We confirmed that these fractal morphology is retained after long-term CO 2 electrolysis under negative bias, as observed by SEM analysis of the post-reacted f-Bi 2 O 3 ( Figure S10). The XPS analysis of the post-reacted f-Bi 2 O 3 ( Figure S11) reveals the presence of -phase Bi 2 O 3 alongside metallic Bi, which is in line with the literature, [55] where negative potentials applied during CO 2 RR leads to the formation of metastable oxide species/interfaces that play a role in the CO 2 RR pathway. Interestingly, the TEM imaging of the post-reacted f-Bi 2 O 3 indicates that the surface of these f-Bi 2 O 3 are reduced to metallic Bi while the core remains oxidized (Figure S11).…”
Section: Resultssupporting
confidence: 88%
“…[37,54] We confirmed that these fractal morphology is retained after long-term CO 2 electrolysis under negative bias, as observed by SEM analysis of the post-reacted f-Bi 2 O 3 ( Figure S10). The XPS analysis of the post-reacted f-Bi 2 O 3 ( Figure S11) reveals the presence of -phase Bi 2 O 3 alongside metallic Bi, which is in line with the literature, [55] where negative potentials applied during CO 2 RR leads to the formation of metastable oxide species/interfaces that play a role in the CO 2 RR pathway. Interestingly, the TEM imaging of the post-reacted f-Bi 2 O 3 indicates that the surface of these f-Bi 2 O 3 are reduced to metallic Bi while the core remains oxidized (Figure S11).…”
Section: Resultssupporting
confidence: 88%
“…We also carried out a thorough mechanistic investigation into the oxygen vacancy defects by synthetically manipulating the amount of defects in flame‐sprayed SnO 2 catalyst. Our results indicate a strong correlation with catalytic activity and the amount of oxygen hole centers, highlighting the importance of defect engineering for CO 2 RR in traditional catalysts …”
Section: Active Sites In Metal‐based Catalystsmentioning
confidence: 61%
“…Data from refs. . The detailed catalytic activity of these catalysts is presented in Table S3 (Supporting Information).…”
Section: Active Sites In Metal‐based Catalystsmentioning
confidence: 99%
“…prepared SnO 2 nanoparticles using flame spray pyrolysis and manipulated the concentration of oxygen hole centres and surface area by tuning the precursor feed rate due to incomplete combustion (Figure 5). [76] These oxygen hole centres arise from the cleavage of the Sn−O−Sn or the Sn−OH links, which results in additional electrons that could be trapped in the vacancies or donated to adjacent metal sites. This results in an electron‐rich catalyst surface which promotes CO 2 adsorption and lowers activation energy for the subsequent CO 2 reduction.…”
Section: Dft Calculations On Sn‐based Catalysts For Co2 Reductionmentioning
confidence: 99%